Cutaneous schistosomiasis: epidemiological and clinical characteristics in returning travelers. (12th September 2022) - Iriarte, Christopher; Marks, Dustin H.
Abstract: The clinical manifestations of parasitic diseases are well‐covered in the infectious disease literature; however, cutaneous manifestations often receive limited attention. There is a need to update existing knowledge and improve reporting of disease characteristics. Given continued increases in travel and transportation, more individuals are acquiring cutaneous infections while traveling abroad. Schistosomiasis is the second most important tropical disease among returning travelers and affects more than 200 million individuals worldwide. The literature classically describes three forms of skin disease in those infected with Schistosoma : the immediate pruritic eruption of cercarial dermatitis, the urticarial response of Katayama syndrome, and the granulomatous lesions of late cutaneous schistosomiasis. Over the last two decades, more atypical presentations have been described. Travelers returning from Africa, South America, and Asia are at highest risk given these are the continents in which the parasite is endemic. This review highlights the cutaneous manifestations of schistosomiasis, with a focus on international travelers with atypical presentations. Additionally, genital schistosomiasis will be reviewed given its significant morbidity. The aim of this review is to update the current body of literature. Dermatologists and other physicians evaluating the skin should be aware of the following principles regarding schistosomal infections: (i) the importance of an early skin biopsy in making the diagnosis; (ii) the necessity of adding schistosomiasis to the differential diagnosis for zosteriform lesions; (iii) the resemblance of chronic cutaneous schistosomiasis of the genitals to sexually transmitted infections; and (iv) the need to revise definitions for early and late infection, specifically for cutaneous disease.